Autopsy methodology in the process of confronting COVID-19 - Teresita Montero González; José Domingo Hurtado de Mendoza Amat; Yusleidis Fraga Martínez; Yamile Torres Gómez; Liem Laguna Oliva (Revista Cubana de Medicina Militar)
Autopsy, the most complete method for the study of diseases, is necessary in epidemic contingencies due to its contributions in the study of causes of death. The purpose of the authors is to show the experiences in the preparation and realization of the autopsies in the confrontation with the COVID-19 in a hospital of attention to patients with suspicion and confirmed in the epidemic. The experience in the organization and execution of the autopsies of deceased suspects and positive to COVID-19 at the Hospital Militar Central Dr. Luis Díaz Soto, carrying out the procedures under biosafety conditions, the diagnostic work and discussion of the results. In this process, the use of the specialized computerization media and the discussions and analysis of deceased were maintained, including as part of the debates in the special working group of the specialty at the national level. Carrying out autopsies of deceased suspects or confirmed COVID-19 patients, even under special conditions, in the context of the pandemic has provided important results for the analysis of mortality in the country. It is important to highlight the value of discussions of mortality analysis that enrich the results.